Reprogramming Yarrowia lipolytica metabolism for efficient synthesis of itaconic acid from flask to semipilot scale - Fu,J; Zaghen,S; Lu,H; Konzock,O; Poorinmohammad,N; Kornberg,A; Ledesma-Amaro,R; Koseto,D; Wentzel,A; Di,Bartolomeo F; Kerkhoven,EJ (Science Advances, 2024)
Itaconic acid is an emerging platform chemical with extensive applications. Itaconic acid is currently produced by Aspergillus terreus through biological fermentation. However, A. terreus is a fungal pathogen that needs additional morphology controls, making itaconic acid production on industrial scale problematic. Here, we reprogrammed the Generally Recognized As Safe (GRAS) yeast Yarrowia lipolytica for competitive itaconic acid production. After preventing carbon sink into lipid accumulation, we evaluated itaconic acid production both inside and outside the mitochondria while fine-tuning its biosynthetic pathway. We then mimicked the regulation of nitrogen limitation in nitrogen-replete conditions by down-regulating NAD+-dependent isocitrate dehydrogenase through weak promoters, RNA interference, or CRISPR interference. Ultimately, we optimized fermentation parameters for fed-batch cultivations and produced itaconic acid titers of 130.1 grams per liter in 1-liter bioreactors and 94.8 grams per liter in a 50-liter bioreactor on semipilot scale. Our findings provide effective approaches to harness the GRAS microorganism Y. lipolytica for competitive industrial-scale production of itaconic acid.